Peningkatan Pengetahuan Petani Melalui Pelatihan Teknik Pemilihan dan Penanaman Benih Kunyit yang Berkualitas di Desa Ramadana - Maria Gorety Landu Wohangara; Karel Yesaya Mbaba; Rusnianti Rambu Lika; Hilarius Ino Dowa (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Turmeric (Curcuma longa L.) is a rhizome crop with high economic value and is widely used in traditional medicine, functional foods, cosmetics, and herbal beverages. Farmers in Ramadana Village face challenges related to limited knowledge in selecting quality seed rhizomes and applying appropriate cultivation techniques. This community service program aimed to improve farmers' knowledge and skills regarding quality turmeric seed selection and proper planting techniques. The methods used included socialization, counseling, field demonstrations, technical training, and mentoring activities. The program was conducted using a participatory approach involving farmers as active participants. The results indicated an improvement in farmers’ understanding of quality seed criteria, land preparation, planting distance, and crop maintenance practices. Farmers were also able to independently select quality seed rhizomes and apply recommended cultivation techniques. This program positively contributed to increasing farmers’ capacity and served as an initial step toward improving turmeric productivity and economic value in Ramadana Village.